2007
DOI: 10.1111/j.1439-0396.2006.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and parameters of microflora in intestinal and faecal samples of piglets due to application of a phytogenic feed additive

Abstract: A commercial phytogenic feed additive (PFA), containing the fructopolysaccharide inulin, an essential oil mix (carvacrol, thymol), chestnut meal (tannins) and cellulose powder as carrier substance, was examined for effects on growth and faecal and intestinal microflora of piglets. Two experiments (35 days) were conducted, each with 40 male castrated weaned piglets. In experiment 1, graded levels of the PFA were supplied (A1: control; B1: 0.05% PFA; C1: 0.1% PFA; D1: 0.15% PFA) in diets based on wheat, barley, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
4
26
0
1
Order By: Relevance
“…Previous studies, regarding the effects of EO and enzymes on growth performance in piglets, are not always consistent. Similar to present study, EO and XB supplementation did not improve ADG in piglets fed wheat barley-based diets (Muhl and Liebert, 2007;Owusu-Asiedu et al, 2010). In contrast, increased growth performance was reported by other authors (Fan et al, 2009;Maenner et al, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies, regarding the effects of EO and enzymes on growth performance in piglets, are not always consistent. Similar to present study, EO and XB supplementation did not improve ADG in piglets fed wheat barley-based diets (Muhl and Liebert, 2007;Owusu-Asiedu et al, 2010). In contrast, increased growth performance was reported by other authors (Fan et al, 2009;Maenner et al, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…In an in vivo anti-bacterial study, Thapa et al (2012) concluded that beneficial commensal Faecalibacterium rausnitzii was sensitive to essential oils at similar or even lower concentrations than the pathogens. In addition, Cross et al (2007) and Muhl & Liebert (2007) reported that essential oils had no effect on the microbial population and composition in the digestive tract or faecal excretions of broilers. The inconsistency of blend application, especially in terms of growth performance, might be because of differences in the buffering capacity value of the diets.…”
Section: Resultsmentioning
confidence: 99%
“…Kohlert et al (2000) observed that the absorption of thymol in humans occurs in the upper intestine. In pigs, essential oils can be absorbed in the proximal portion of the intestine, and therefore, the antimicrobial activity in the distal portion of the intestine is limited (Muhl and Liebert, 2007). Thus, these factors may also influence the use of active principles present in the additive under study in this experiment because little information about the absorption modes of these substances through the digestive tract of tilapia is available.…”
Section: Resultsmentioning
confidence: 91%
“…Probiotics used in broilers showed a final weight and weight gain similar to observations in animals supplemented with antibiotic growth promoters (Çabuk et al, 2006(Çabuk et al, , Traesel et al, 2011. Muhl and Liebert (2007) inclusion of a phytogenic additive in pig diets did not improve the performance or intestinal microflora of piglets. Hashemi and Davoodi (2010) and Hernandez et al (2004) attributed the positive effects of plant extracts on growth performance and nutrient digestibility to the appetite and digestion-stimulating and antimicrobial properties of these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation